Changes in classic and alternative pathways of bile acid synthesis in chronic liver disease - Crosignani, Andrea; Del Puppo, Marina; Longo, Matteo; De Fabiani, Emma; Caruso, Donatella; Zuin, Massimo; Podda, Mauro; Javitt, Norman B.; Kienle, Marzia Galli (Clinica chimica acta, 2007)
Cholesterol elimination occurs through bile acid synthesis that starts within the liver from 7α-hydroxylation or in extrahepatic tissues from 27-hydroxylation. This study was aimed at investigating in vivo these two pathways in patients with chronic liver disease. Serum concentrations of 7α- and 27-hydroxycholesterol were measured in 54 patients (29 with primary biliary cirrhosis and 25 with chronic hepatitis C) and 18 controls. The rate of oxysterol plasma appearance was calculated after intravenous infusions of deuterated 7α- and 27-hydroxycholesterol in patients ( n = 8) and control subjects ( n = 8) who gave consent. The expression of sterol 27-hydroxylase was evaluated in macrophages isolated from 20 subjects. In patients with liver disease, the rate of plasma appearance of 7α-hydroxycholesterol was significantly reduced (1.44 ± 0.96 vs. 2.75 ± 1.43 mg/hour, p = 0.03), the degree of reduction being related with the severity of the disease ( p = 0.01) whereas that of 27-hydroxycholesterol was unaffected. The rate of plasma appearance of 27-hydroxycholesterol was significantly related to its serum concentrations ( r = 0.54, p = 0.03) and to its release from cultured macrophages ( r = 0.85, p = 0.03). In liver disease 7α-hydroxylation of cholesterol seems to be impaired while 27-hydroxylation is unaffected. Serum concentrations of 27-hydroxycholesterol are useful to obtain information on the activity of this alternative pathway.